What is Specific about Art/Cultural Projects? - Ljiljana Deru Simic (Fondazione Eni Enrico Mattei (FEEM), 2003)
The present issue focuses on the contribution made by art/cultural initiatives to the development of multiple identity in some of the European cities having in mind the subjectivity of the artists and plurality of the surrounding cultures. The art/cultural projects (AES- Russia, Europe Art Train Holland, Life Station Austria and some others) with intercultural dimension have a special character to offer because: they are dealing with meaning, and enable dialogue between people in different social groups. The examples will be taken from different European countries, which aim to reinterpret the reality of life, to show, answer, and question its contradictions. The attention will be focused on their political, educational and aesthetic contribution to the community construction having in mind their desire for new intercultural policy and practices. Every artist crosses borders daily but those who choose to cross cultural borders (language, expression, music, tradition) enter into a fertile, but dangerous field. Artists do not aim specifically to produce multicultural work but since they are living in specific time, and since art is rooted in real life, the realities of everyday life are transposed into their work. This paper is fundamentally interested in the role that art projects can play in a modern society and promotes the initiative that links an artistic dimension to a form of interactive social urban situation. All projects are representing laboratories' that use public spaces. It is more than obvious that the social and the economic fields are not separated from the cultural one beside the tendency that is putting them in opposition as artists and the world rather than artists in the world. In the last two decades, the world of the arts has economised rapidly. Increasingly, artists have turned the economy into a subject of their own work. Art/cultural projects engage people's creativity, and so lead to problem-solving. They encourage questioning, and the imagination of possible future actions. They offer self-expression, which is an essential characteristic of the active citizen. Some experiences from the art/cultural field are shifting attention towards the people themselves: their imagination, motivation, demands, fantasies and only then the city is becoming a cultural product, a community construction.
Keywords: Z10; 330; Intercultural actions; Policy agenda; Art/cultural projects; Networking aspects